Epidemiology and risk factors associated with deaths from tuberculosis in older people who live in the capital of the Northeastern part of Brazil - Vasconcelos, Jônatas Carneiro; Saintrain, Maria Vieira de Lima; Lima, Ana Ofélia Portela; Florêncio, Caroline Mary Gurgel Dias; Bruno, Zenilda Vieira; de Moura, Walda Viana Brígido (International Journal of Advanced Engineering Research and Science, 2020)
Introduction: Tuberculosis (TB) is an extreme relevance pathology to the Public Health due to the morbidity and mortality high rates, with emphasis on the older population. The bacillus characteristic is intracellular, so a competent immune system must be needed to fight it through the cellular mechanisms. Methods: Cross-sectional, documentary and analytical study based on the review of 128 medical records from the patients, who aged 60 years old or older at the time of the care due to TB or its complications from January 2006 to December 2016. Results:The death prevalence was 44.5%. The bivariate analysis revealed that the men died 30% more than the women (PR = 1.3; CI 95% 0.81 - 2.07). In regard to the outcome (death and discharge), there was a statistical significance related to: a) clinical and epidemiological characteristics: Outpatient care (p = 0.002), ICU (p <0.001), Coma (p = 0.005), Hospitalization days (p <0.001 ), Treatment Adherence (p = 0.006), Treatment Abandonment (p = 0.036); b) risk and some associated factors: Malnutrition (p = 0.018), Hypertension (p = 0.024), HIV / AIDS (p = 0.010); The Poisson regression model for the outcome death / discharge shows ICU admission (p<001), Treatment adherence (p=002), Procedence origin (p=046). Conclusion: The study showed different risk factors toward the death occurrence from the tuberculosis amog the older people and illustrates the relevance of a continuous surveillance in order to monitor the TB.